Benefits of Biblical Interpretation to Christians - Queen Ijeoma Sokwaibe; Emmanuel Chukwujindu Asogwa (Nsukka Journal of Religion and Cultural Studies, 2022)
Biblical interpretation is the act of interpreting the bible for further understanding. It involves figuring out what God, through His human authors, wanted the biblical text to signify and accomplish. Exegesis and theology are used to evaluate, summarise, and apply God’s inerrant word. This process involves both the more focused task of figuring out what God was actually saying through the human authors in particular passages and the more general task of connecting this message to God’s overarching plan for redemption that culminates in Christ, with specific application to current situation. This study therefore clarifies biblical interpretation and its benefits to the contemporary Christian church. Thus, it synthesises what presuppositions should guide our interpretation of a biblical text, and the role it plays in the lives of bible believing Christians. This paper utilised historical and descriptive approaches in its research, and explains the various methods and tools of biblical criticism. The study posits that heretical teachings have been a big problem facing the Christian society for long, and it exists because of misinterpretation of the scriptures. Proper biblical interpretation helps Christians avoid the mistakes of misleading one another thereby reducing the rate of false teaching and religious fanatics. With proper interpretation, the Christian bible comes to be seen as not just a book but a book of moral instructions for the life lived by all Christian and yet to be lived by posterity. The paper recommends that the acquaintance with biblical hermeneutics and criticism would give better insight in understanding biblical theology. This will as such reduce the rate at which heretical teaching gets indoctrinated among many Christians today.